Indoor air quality in California homes with code‐required mechanical ventilation. (11th May 2020) - Singer, Brett C.; Chan, Wanyu R.; Kim, Yang‐Seon; Offermann, Francis J.; Walker, Iain S.
Abstract: Data were collected in 70 detached houses built in 2011‐2017 in compliance with the mechanical ventilation requirements of California's building energy efficiency standards. Each home was monitored for a 1‐week period with windows closed and the central mechanical ventilation system operating. Pollutant measurements included time‐resolved fine particulate matter (PM2.5 ) indoors and outdoors and formaldehyde and carbon dioxide (CO2 ) indoors. Time‐integrated measurements were made for formaldehyde, NO2, and nitrogen oxides (NOX ) indoors and outdoors. Operation of the cooktop, range hood, and other exhaust fans was continuously recorded during the monitoring period. Onetime diagnostic measurements included mechanical airflows and envelope and duct system air leakage. All homes met or were very close to meeting the ventilation requirements. On average, the dwelling unit ventilation fan moved 50% more airflow than the minimum requirement. Pollutant concentrations were similar to or lower than those reported in a 2006‐2007 study of California new homes built in 2002‐2005. Mean and median indoor concentrations were lower by 44% and 38% for formaldehyde and 44% and 54% for PM2.5 . Ventilation fans were operating in only 26% of homes when first visited, and the control switches in many homes did not have informative labels as required by building standards.